The effect of the Inositol model on the development of convergent thinking among second grade students in Arabic grammar - Ahmed Ali Al-Azzawi, Ahmed Fares (Journal of Tikrit University for Humanities, 2023)
The current study aimed to find out “the effect of the Entostel model on developing convergent thinking among second-year intermediate students in Arabic grammar.” To achieve this, the researcher chose Al-Khadra Secondary School for Boys, The research sample consisted of (62) students in the second intermediate year, with (31) students in the experimental group and (31) students in the control group. The researcher formulated (78) behavioral goals within the six levels of Bloom’s taxonomy in the cognitive field. The researcher prepared a convergent thinking test consisting of (35) items. The psychometric properties of the test were confirmed, and after processing the data statistically using the statistical package, the study reached the following results: The students of the experimental group who studied according to the Entostel model outperformed the students of the control group who studied according to the usual method in the convergent thinking test. In the light of the results of this research, the researcher concludes that teaching grammar subjects according to the Intostel model in terms of its sequential steps contributed to the cognitive increase of the second intermediate grade students in the grammar subject and led to the development of their convergent thinking. The researcher recommends holding training courses for grammar teachers, male and female, and learning about this model of teaching and knowing its steps, as well as learning how to prepare, plan, and implement it in teaching grammar. The researcher proposes to conduct the following studies: The effect of the Entostel model on the achievement and development of divergent thinking skills among fourth-year literary students in the subject of literature and texts.